SOSIALISASI DAN PELATIHAN MITIGASI BENCANA ALAM MELALUI MEDIA INFOGRAFIS - Reny Wiyatasari; S.I. Trahutami (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
The purpose of this service’s activity to society is to provide knowledge and understanding of the importance of disaster mitigation. Like Japan, which has a lot of experience as a country that often experiences disasters, such as earthquakes and tsunamis, knowledge and understanding are instilled early on, that is, since children enter school, so that when a disaster does occur, everyone already has the ability and knowledge about disaster response. Therefore, it is deemed necessary to conduct socialization regarding disaster mitigation to the community members who live in Bendungan Village, Tretep Subdistrict, Temanggung Regency because geographically it also has the potential to experience natural disasters. Knowledge about how to act or anticipate in the event of an earthquake is believed to be very useful if owned by an individual or group.Keywords : Japan, disaster mitigation, disaster response